Investigation of osmotic shock effect on pulsed electric field treated S. cerevisiae yeast cells - Gančytė, Greta; Šimonis, Povilas; Stirkė, Arūnas (Nature Research, 2023)
Pulsed electric field (PEF) treatment is known to cause plasma membrane permeabilization of microorganisms, an effect known as electroporation. PEF treatment is very attractive since it can achieve permeabilization with or without lethal damage in accordance with desired results. This study aimed to expand the accomplishment of electroporation outcomes by applying sudden post-PEF osmotic composition change of the media. Changes in yeast cells’ viability, size and plasma membrane regeneration rate were evaluated. However, we still have questions about the intracellular biochemical processes responsible for plasma membrane recovery after electroporation. Our suggested candidate is the high osmolarity glycerol (HOG) kinase pathway. The HOG pathway in Saccharomyces cerevisiae yeasts is responsible for volume recovery after dangerous shape modifications and intracellular water disbalance caused by environmental osmotic pressure changes. Thus, we evaluated the HOG pathway inactivation effect on S. cerevisiae’s reaction to PEF treatment. Results showed that Hog1 deficient S. cerevisiae cells were considerably more sensitive to electric field treatment, confirming a link between the HOG pathway and S. cerevisiae recovery process after electroporation. By suddenly changing the osmolarity of the media after PEF we influenced the cells’ plasma membrane recovery rate, severity of permeabilization and survivability of yeast cells. Studies of electroporation in combination with various treatments might improve electric field application range, efficiency, and optimization of the process. © 2023, The Author(s). --//-- This is an open access article Gančytė, G., Šimonis, P. & Stirkė, A. Investigation of osmotic shock effect on pulsed electric field treated S. cerevisiae yeast cells. Sci Rep 13, 10573 (2023). https://doi.org/10.1038/s41598-023-37719-4 published under the CC BY 4.0 licence.
A.S. acknowledges the ERDF PostDoc project No. 1.1.1.2/VIAA/4/20/739. Authors are grateful to Dr. Tom Yager for proofreading the manuscriptInstitute of Solid State Physics, University of Latvia as the Center of Excellence is supported through the Framework Program for European universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES